A Study on the Education Assistant System Using Smartphones and Service Robots for Children. (30th April 2014) - Jeong, Gu-Min; Park, Chang-Woo; You, Sujeong; Ji, Sang-Hoon
In this paper, we propose a new education assistant system model using both smartphones and service robots for children's learning. Through the interaction between a smartphone and a robot, various use cases can be derived. For example, we can control the movement of the robot remotely, watch the status of the children using real-time streaming, or read the answer on the smartphone while only the question is displayed on the robot. Considering these facts, we present three use cases, namely 'remote control', 'streaming' and 'N-screen' for robot-based learning with smartphones. The proposed learning model is implemented in Android-based smartphones and a service robot using the OPRoS platform, and we show that the proposed model works well. 1